Unemployment benefit governance, trade unions and outsider protection in conservative welfare states. (May 2022) - Clegg, Daniel; Heins, Elke; Rathgeb, Philip
This article explores the relationship between trade union governance roles in unemployment benefit systems, their power resources and their capacity to counteract liberalising and dualising trends in the labour market in conservative welfare states with compulsory unemployment insurance. Against received wisdom, this article argues that in the 21st century trade unions in continental Europe have generally sought to combat the dualism to which their welfare states and labour markets are institutionally susceptible. In this context, a role in the operation of unemployment benefit systems and related forms of institutional power could help unions to attain the enhanced outsider protection they seek. But different modes of union involvement in public policy produce different levels of institutional power, and help to condition its impact on policy development over time. This article illustrates these points with a comparison of the recent development of labour market policy and regulation in Austria, France and Germany.